Market society and the institutional theory of Karl Polanyi - Cangiani, Michele (Institutional Economics: Perspectives and Methods in Pursuit of a Better World, 2021)
This chapter examines Polanyi’s institutional theory of market-capitalist society. It shows that market society is, according to Polanyi, a peculiarly “economic” society: its economy appears both autonomous and dominant, constraining the structure and evolution of other social subsystems. The chapter also demonstrates that Polanyi’s theory and method allow an explanation of the institutional transformations of market society. In the face of today’s great economic difficulties, social uneasiness, and ecological distress, Polanyian institutionalism remains a rich source of insight on humanity’s challenges and possibilities.

Going public with Polanyi in the era of Trump * - Burawoy, Michael (The Routledge International Handbook of Public Sociology, 2021)
After considering different possible elements of the ‘Trump era,’ I will turn to The Great Transformation to periodize capitalism into three waves of marketization and their counter-movements. In the first wave, we follow the commodification of land, money and especially labor, so-called fictitious commodities, and the local counter-movements marketization inspired, reaching to the level of the state. In the second wave, the focus turns on the way marketization generated a reaction from states, seeking to regulate commodification – in other words, processes of de-commodification. Given the tension between capitalism and democracy, in Polanyi’s view essentially two forms of regulation were possible: either democracy suppresses capitalism and we get socialism, or capitalism suppresses democracy and we get fascism. He neither paid much attention to the popular forces that led in either direction nor to the possibility of a compromise between capitalism and democracy that reigned in three decades after World War Two. Beginning in the 1970s, we witnessed the beginning of a third wave of marketization – more commonly known as neoliberalism – that Polanyi did not anticipate. I attribute his failure to anticipate another wave of marketization to the contradictory pressures of accumulation that are temporarily alleviated by commodification. In this third wave, I show how democracy is discredited, and consensus politics dissolves into polarizing movements within and beyond parliamentary politics. The lived experience driving these movements, I argue, revolves around processes of re-commodification and ex-commodification of nature, money, labor and knowledge. This is the terrain upon which sociology must engage its publics. I highlight two approaches, both founded on an organic public sociology that engages directly with publics. On the one hand, there is the empathic public sociology that wades into communities in order to comprehend the distinctive ‘deep narrative’ of right wing populism, typified by Arlie Hochschild’s Strangers in Their Own Land. On the other hand, there is the affirmative public sociology that creates a collective vision based on a dialogue with the practitioners of real utopias, typified by Erik Wright’s How to Be an Anti-Capitalist in the Twenty-First Century.
Keywords: Trumpism; marketization; public sociology

Karl Polanyi: The Great Transformation - Ebner, Alexander (Schlüsselwerke der Wirtschaftssoziologie, 2021)
Karl Polanyi war in jungen Jahren Zeitzeuge der vielschichtigen ökonomischen, sozialen und politischen Umwälzungen in der österreichisch-ungarischen Donaumonarchie. 1886 in Wien geboren, wuchs er in Budapest auf, wo er Rechtswissenschaft und Philosophie studierte, um dann nach der Zerschlagung der ungarischen Räterepublik nach Wien zurückzukehren. Dort schrieb er für die wirtschaftspolitische Wochenzeitschrift „Österreichischer Volkswirt“.
Keywords: biography